Ответы и объяснения

2012-12-17T16:43:00+00:00

\left \{ {{x^2-3y^2=1} \atop {x-2y=1}} \right. \\ \\\left \{ {{(1+2y)^2-3y^2=1} \atop {x=1+2y}} \right. \\ \\\left \{ {{4y+y^2=0} \atop {x=1+2y}} \right. \\ \\\left \{ {{y(4+y)=0} \atop {x=1+2y}} \right. \\ \\\begin{cases} y=0\\y=-4\\x=1+2y \end{cases} \\ \\\begin{cases} y=0\\y=-4\\x=1+2*0\\x=1+2*(-4) \end{cases}\\ \\ \\\begin{cases} y=0\\y=-4\\x=1\\x=-7 \end{cases}

 

 

Ответ: (x=-7 y=-4) (x=1 y=0)

 

 

\begin{cases} x^2+3xy-3y^2=1\\2x^2-xy+x^2=2 \end{cases} \\ \\\begin{cases} x^2+3xy-3y^2=1\\6x^2-3xy+3y^2=6 \end{cases} \\ \\\begin{cases} x^2+3xy-3y^2=1\\7x^2=7 \end{cases} \\ \\\begin{cases} x^2+3xy-3y^2=1\\x=1\\x=-1 \end{cases} \\ \\\begin{cases} 1+3y-3y^2=1\\1-3y-3y^2=1\\x=1\\x=-1 \end{cases} \\ \\\begin{cases} 3y-3y^2=0\\-3y-3y^2=0\\x=1\\x=-1 \end{cases} \\ \\\begin{cases} y(3-3y)=0\\-y(3+3y)=0\\x=1\\x=-1 \end{cases} \\ \\\begin{cases} y=1\\y=-1\\y=0\\x=1\\x=-1 \end{cases}

 

Ответ: (x=-1 y=-1) (x=-1 y=0) (x=1 y=0) (x=1 y=1)